Duloxetine in Psychiatric Disorders: Expansions Beyond Major Depression and Generalized Anxiety Disorder - Muscatello, Maria Rosaria Anna; Zoccali, Rocco A.; Pandolfo, Gianluca; Mangano, Paolo; Lorusso, Simona; Cedro, Clemente; Battaglia, Fortunato; Spina, Edoardo; Bruno, Antonio (Frontiers in Psychiatry, 2019)
Background: Duloxetine hydrochloride (DUL) is an antidepressant included in the pharmacological class of serotonin–norepinephrine reuptake inhibitors approved for the treatment of major depressive disorder, generalized anxiety disorder, diabetic peripheral neuropathic pain, fibromyalgia, and chronic musculoskeletal pain. The aim of this review was to elucidate current evidences on the use of DUL in the treatment of a variety of psychiatric disorders. Methods: This systematic review was conducted according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. PubMed database was searched from January 1, 2003, to September 30, 2018, using 11 key terms related to psychiatric disorders (“persistent depressive disorder,” “dysthymic disorder,” “bipolar disorder,” “seasonal affective disorder,” “obsessive-compulsive disorder,” “social phobia,” “panic disorder,” “posttraumatic stress disorder,” “schizophrenia,” “eating disorders,” “sexual disorders,” “personality disorders”) and one key term related to duloxetine (“duloxetine hydrochloride”). Article titles and abstracts were scanned to determine relevance to the topic. For additional studies, the authors also examined the reference lists of several of the included papers. Results: Duloxetine may be an effective treatment for mood spectrum disorders, panic disorder, several symptom clusters of borderline personality, and as add-on drug in schizophrenia. Modest or conflicting results have been found for the efficacy of duloxetine in obsessive–compulsive disorder, posttraumatic stress disorder, eating, and sexual disorders. Conclusion: Major limitations of the reviewed studies were short trial duration, small sample sizes, and the lack of control groups. Defining the potential role of DUL in the treatment of psychiatric disorders other than major depressive disorder and generalized anxiety disorder needs further randomized, placebo-controlled studies.